Vitality and continuity of family businesses - Rydvalova, Petra; Antlova, Klara (Journal of Business Economics and Management, 2020)
The article aims to explain the reasons and the methods for evaluating the vitality of the family businesses with a focus on a country where family businesses were violently interrupted by forty years of the socialist regime. The intention is to find out, in connection with the vitality of family businesses, whether it is possible to define the factors that enabled the subsequent continuity of this type of business, for instance, the sector that is relevant to the region. The authors draw on a resource-based view as well as the specifics of the family-owned business in an institutional context. They comment on the behaviour of family business from three perspectives – legal, managerial and economic. The intention of knowledge/evaluation system presented is to find the weaknesses in the family business structures in the Czech Republic, which opens the opportunity for the succession process and the subsequent professionalization of their solutions. The methodology is presented in ten case studies. The results of the evaluation showed considerable compliance with those assumptions defined in the literature on those family businesses that continued uninterrupted.